Invitation to the Secret Buddha of Zenkōji: Kaichō and Religious Culture in Early Modern Japan - Hur, Nam-lin (Japanese journal of religious studies, 2009)
In early modern Japan, for Buddhist temples endowed with famed "secret Buddhas," the kaichō was a lucrative means of public fundraising. In particular, at a time when a large-scale project such as building or repairing a Main Hall required sizable funding, many temples often turned to holding kaichō events, during which lay Buddhists evinced a spectacular enthusiasm for the secret Buddhas that were on display. Through the example of Zenkōji, this article reveals that the popularity of kaichō, which was unique to Japanese Buddhist culture, was fostered as well as manipulated within traditional Japanese ideas regarding yorishiro (lodging place), saijitsu (ritual date), and marebito (visitordeity). The aura of secrecy and mystery surrounding, and inseparable from, kaichō deities was used not only for the benefit of kaichō temples but also for the benefit of kaichō visitors.